2021
DOI: 10.3389/feart.2021.739365
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and Geochemical Evidence of Permafrost Formation at Mamontova Gora and Syrdakh, Central Yakutia

Abstract: Biotracers marking the geologic history and permafrost evolution in Central Yakutia, including Yedoma Ice Complex (IC) deposits, were identified in a multiproxy analysis of water chemistry, isotopic signatures, and microbial datasets. The key study sections were the Mamontova Gora and Syrdakh exposures, well covered in the literature. In the Mamontova Gora section, two distinct IC strata with massive ice wedges were described and sampled, the upper and lower IC strata, while previously published studies focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 96 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…At present, Yedoma covers ~1,387,000 km 2 or ~6% of the permafrost region in the Northern Hemisphere (~23 × 10 6 km 2 ) 6 . Yedoma is particularly abundant in eastern Siberia and Alaska, 7 but also in central Yakutia 8–12 . Despite its relatively small proportions, the organic‐rich Yedoma preserves ~327–466 Gt of organic carbon, 6,13 accounting for over ~25% of organic carbon stored in northern high‐latitude permafrost (~1,140–1,476 Gt) 1 .…”
Section: Introductionmentioning
confidence: 99%
“…At present, Yedoma covers ~1,387,000 km 2 or ~6% of the permafrost region in the Northern Hemisphere (~23 × 10 6 km 2 ) 6 . Yedoma is particularly abundant in eastern Siberia and Alaska, 7 but also in central Yakutia 8–12 . Despite its relatively small proportions, the organic‐rich Yedoma preserves ~327–466 Gt of organic carbon, 6,13 accounting for over ~25% of organic carbon stored in northern high‐latitude permafrost (~1,140–1,476 Gt) 1 .…”
Section: Introductionmentioning
confidence: 99%
“…A similar phenomenon was observed in clay permafrost layer from Western Spitsbergen [ 95 ] and the CRREL Permafrost Tunnel, Alaska, United States [ 96 , 97 ]. The authors of these manuscripts suggested that these taxa could be the markers of climate change; in particular, Firmicutes mark synergetic freezing of sediments (hypothesis of a marker of syngenetic sediment formation) [ 98 ]. Most likely, the unusually high contribution of Firmicutes , with a decrease in Chloroflexota , in the investigated St7Grf6 core could be due to the influence of turbidites that were common in the sediments of the northern basin of Lake Baikal and that could had been formed during the advance and retreat of glaciers in the Late Pleistocene [ 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%